Impact of Angiotensin Type 1A Receptors in Principal Cells of the Collecting Duct on Blood Pressure and Hypertension. Issue 6 (June 2016) - Chen, Daian; Stegbauer, Johannes; Sparks, Matthew A.; Kohan, Donald; Griffiths, Robert; Herrera, Marcela; Gurley, Susan B.; Coffman, Thomas M.
Abstract : The main actions of the renin–angiotensin system to control blood pressure (BP) are mediated by the angiotensin type 1 receptors (AT1 Rs). The major murine AT1 R isoform, AT1A R, is expressed throughout the nephron, including the collecting duct in both principal and intercalated cells. Principal cells play the major role in sodium and water reabsorption. Although aldosterone is considered to be the dominant regulator of sodium reabsorption by principal cells, recent studies suggest a role for direct actions of AT1 R. To specifically examine the contributions of AT1A R in principal cells to BP regulation and the development of hypertension in vivo, we generated inbred 129/SvEv mice with deletion of AT1A R from principal cells (PCKO). At baseline, we found that BPs measured by radiotelemetry were similar between PCKOs and controls. During 1-week of low-salt diet (<0.02% NaCl), BPs fell significantly ( P <0.05) and to a similar extent in both groups. On a high-salt (6% NaCl) diet, BP increased but was not different between groups. During the initial phase of angiotensin II–dependent hypertension, there was a modest but significant attenuation of hypertension in PCKOs (163±6 mm Hg) compared with controls (178±2 mm Hg; P <0.05) that was associated with enhanced natriuresis and decreased alpha epithelial sodium channel activation in the medulla of PCKOs. However, from day 9 onward, BPs were indistinguishable between groups. Although effects of AT1A R on baseline BP and adaptation to changes in dietary salt are negligible, our studies suggest that direct actions of AT1A R contribute to the initiation of hypertension and epithelial sodium channel activation. Abstract : Supplemental Digital Content is available in the text.